2020
DOI: 10.5435/jaaosglobal-d-20-00169
|View full text |Cite
|
Sign up to set email alerts
|

Spica Casting Results in More Unplanned Reoperations than Elastic Intramedullary Nailing: A National Analysis of Femur Fractures in the Preschool Population

Abstract: Background: Spica casting and elastic stable intramedullary nailing (ESIN) are treatment options for femur fractures in preschool-age children. Clinical practice guidelines are only of moderate or limited strength, which may lead to variation in practice. The purpose of this study was to compare the revision surgery rate in young children undergoing these procedures. Methods: The Pediatric Health Information System, a database of 49 children hospitals, was queried for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The ESIN group was significantly older with an average of 4.5 years [ 13 ]. Brnjos et al found in their database research 1181 children treated with ESIN in femoral shaft fractures with an average age of 4.9 years [ 15 ]. Lewis et al reported 32 patients treated with ESIN at 5.3 years of age in average [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESIN group was significantly older with an average of 4.5 years [ 13 ]. Brnjos et al found in their database research 1181 children treated with ESIN in femoral shaft fractures with an average age of 4.9 years [ 15 ]. Lewis et al reported 32 patients treated with ESIN at 5.3 years of age in average [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ramo et al reported revision surgery in 4% of patients in both groups [ 25 ]. In a recent study, Brnjos et al reported 4.4 times more unplanned reoperations in the non-operative group [ 15 ]. In our study, we had one case of conversion into surgical treatment due to skin lesions after traction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most pediatric femoral shaft fractures in children aged 5 years and older are now treated with internal fixation. 22 During middle childhood (5 to 11 years old), flexible nails are usually the most appealing option for extraphyseal fixation. Flynn et al 25 prospectively compared titanium flexible nails versus traction and a spica cast in 83 patients aged 6 to 16 years.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Hospitalization length and financial expenses remain another issue to compare. However, there are no reported cases on the management of children with transposition of the fractured segments of the femur [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%